Sequencing of Ipilimumab Plus Nivolumab and Encorafenib Plus Binimetinib for Untreated BRAF-Mutated Metastatic Melanoma (SECOMBIT): A Randomized, Three-Arm, Open-Label Phase II Trial. Issue 2 (1st September 2022) - Ascierto, Paolo A.; Mandalà, Mario; Ferrucci, Pier Francesso; Guidoboni, Massimo; Rutkowski, Piotr; Ferraresi, Virginia; Arance, Ana; Guida, Michele; Maiello, Evaristo; Gogas, Helen; Richtig, Erika; Fierro, Maria Teresa; et al.
Abstract : PURPOSE: Limited prospective data are available on sequential immunotherapy and BRAF/MEK inhibition for BRAFV600 -mutant metastatic melanoma. METHODS: SECOMBIT is a randomized, three-arm, noncomparative phase II trial (ClinicalTrials.gov identifier: NCT02631447 ). Patients with untreated, metastatic BRAFV600 -mutant melanoma from 37 sites in nine countries were randomly assigned to arm A (encorafenib [450 mg orally once daily] plus binimetinib [45 mg orally twice daily] until progressive disease [PD] -> ipilimumab plus nivolumab [ipilimumab 3 mg/kg once every 3 weeks and nivolumab 1 mg/kg once every 3 weeks × four cycles -> nivolumab 3 mg/kg every 2 weeks]), arm B [ipilimumab plus nivolumab until PD -> encorafenib plus binimetinib], or arm C (encorafenib plus binimetinib for 8 weeks -> ipilimumab plus nivolumab until PD -> encorafenib plus binimetinib). The primary end point was overall survival (OS) at 2 years. Secondary end points included total progression-free survival, 3-year OS, best overall response rate, duration of response, and biomarkers in the intent-to-treat population. Safety was analyzed throughout sequential treatment in all participants who received at least one dose of study medication. RESULTS: A total of 209 patients were randomly assigned (69 in arm A, 71 in arm B, and 69 in arm C). At a median follow-up of 32.2 (interquartile range, 27.9-41.6) months, median OS was not reached in any arm and more than 30 patients were alive in all arms. Assuming a null hypothesis of median OS of ≤ 15 months, the OS end point was met for all arms. The 2-year and 3-year OS rates were 65% (95% CI, 54 to 76) and 54% (95% CI, 41 to 67) in arm A, 73% (95% CI, 62 to 84) and 62% (95% CI, 48 to 76) in arm B, and 69% (95% CI, 59 to 80) and 60% (95% CI, 58 to 72) in arm C. No new safety signals emerged. CONCLUSION: Sequential immunotherapy and targeted therapy provide clinically meaningful survival benefits for patients with BRAFV600 -mutant melanoma.